A 7‐year‐old boy with toxic epidermal necrolysis, heart failure, and sepsis treated with the guidance of invasive hemodynamic monitoring: A case report. Issue 7 (6th July 2021) - Saeed, Amir; Mehdizadegan, Nima
Abstract: Toxic epidermal necrolysis is a rare immunological disease that is secondary to some medications or upper respiratory infections, with more than 30% involvement of skin and mucosa. Herein, we describe a 7‐year‐old boy with TEN, heart failure, and sepsis treated with the guidance of an invasive hemodynamic monitoring device. Abstract : Toxic epidermal necrolysis is a rare immunological disease that is secondary to some medications or upper respiratory infections, with more than 30% involvement of skin and mucosa. Herein, we describe a 7‐year‐old boy with TEN, heart failure, and sepsis treated with the guidance of an invasive hemodynamic monitoring device.